POTENSI TUMBUHAN OBAT SEBAGAI FITOBIOTIK MULTI FUNGSI UNTUK MENINGKATKAN PENAMPILAN DAN KESEHATAN SATWA DI PENANGKARAN - Maria Ulfah (Media Konservasi, 2006)
Managing the feeding program is the most important concept in feeding of wild animals in captivity to maintain their performance, health condition and absolutely sustainability. Since the use of medicine plants show significantly improvement of the performance and health condition of domesticated animals, it sounds promisingly to use such plants for wild animals in captivity, especially for commercial purposes. Due to their properties, the medicinal plants can be classified as appetite stimulating substances, digestive enhancers, bacterial steering agents, metabolic modifiers and odour neutralizing agents, that is called multi-function phytobiotics (MFP). However further studies should be done to investigate an effectiveness-oriented of active components of medicinal plants on the regulation of performance and health condition of wild animals in captivity.Keywords : Feeding program, wild animal, medicinal plant, Multi Function Phytobiotic, performance, health